Penetrating angle grinder injury to the neck causing subclavian artery injury. (February 2021) - Varley, Vincent; Claydon, Matthew; Solomon, Jarryd; Dean, Anastasia; Lovelock, Thomas; Fitzgerald, Mark C.
Abstract: Penetrating injuries to the neck present a unique challenge due to the confined space of the thoracic outlet for haemorrhage control and repair. This results in high mortality rates when the major vascular structures of the neck are transected, as well as potential neurological compromise. We present the case of a penetrating injury to the proximal subclavian artery from a broken angle grinder disc which is a unique mechanism of injury that can have fatal consequences. The patient described in this case underwent an emergent median sternotomy for proximal control of the brachiocephalic trunk and ligation of the right vertebral artery to facilitate a primary repair of the injured vessel segment. Post operatively the patient made a complete recovery with no central or peripheral neurologic deficits and requiring no further interventions. The key points from this case are that angle grinders pose a significant injury burden and early specialised medical attention should be sought, rapid control of the proximal neck vessels can be obtained via a median sternotomy and that the vertebral artery can be ligated in an emergent situation without neurological consequence.